2018
DOI: 10.6065/apem.2018.23.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autoimmune thyroiditis in patients with type 1 diabetes: a long-term follow-up study

Abstract: PurposeType 1 diabetes mellitus (DM) is associated with autoimmune diseases such as thyroiditis. Therefore, we aimed to investigate the prevalence of autoimmune thyroiditis in patients with type 1 DM.MethodsA total of 102 patients who were diagnosed and followed up (mean age, 8.1±4.0 years) in Ajou University Hospital were enrolled in this study. All the patients were evaluated for beta cell autoimmunity, including insulin autoantibody, glutamic acid decarboxylase antibodies (GADA), and islet cell antibody. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
3
13
1
Order By: Relevance
“…In our study, we were able to show that the association with islet autoantibodies differed between the two thyroid autoantibodies as well as gender. We could confirm the previously described association between TPOAb and GADA in children and adults screened for autoimmunity [34], children and adolescents diagnosed with AITD [35] as well as in patients with type 1 diabetes [10,36,37] and GD [38]. GADA in patients with AITD might not only indicate increased risk for type 1 diabetes, but also be a biomarker that reflects other endocrine autoimmunity like thyroid autoimmunity as GADA has been found associated to thyroid disease in patients with type 2 diabetes [39].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we were able to show that the association with islet autoantibodies differed between the two thyroid autoantibodies as well as gender. We could confirm the previously described association between TPOAb and GADA in children and adults screened for autoimmunity [34], children and adolescents diagnosed with AITD [35] as well as in patients with type 1 diabetes [10,36,37] and GD [38]. GADA in patients with AITD might not only indicate increased risk for type 1 diabetes, but also be a biomarker that reflects other endocrine autoimmunity like thyroid autoimmunity as GADA has been found associated to thyroid disease in patients with type 2 diabetes [39].…”
Section: Discussionsupporting
confidence: 87%
“…ATA appears within 2.5–3 years of disease progression [ 20 ]. Studies assessing the presence of ATA in patients with DM1 differ significantly regarding the incidence of AITD, as presented in Table 4 [ 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that age, female gender, disease duration, and the presence of beta-cell autoimmunity are risk factors for developing AITD in patients with DM1. In studies by Hwang et al and Jin et al, the presence of antiglutamic acid decarboxylase antibodies (GADAs) at the time of DM1 diagnosis was a significant predictor of AITD development [ 24 , 25 ]. However, the exact mechanism by which GADA influences thyroid autoimmunity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, markers of AITDs can also be considered as biomarkers for thyroid function. The presence of autoantibodies, namely thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb), have been measured in individuals who develop autoimmunity [ 21 ]. TPOAb targets the thyroid peroxidase (TPO) enzyme, which is responsible for adding iodine to thyroglobulin (Tg), the precursor of T3 and T4 [ 13 , 22 ] and TgAb targets Tg [ 22 ].…”
Section: Introductionmentioning
confidence: 99%